Estudio de prefactibilidad para brindar servicio de estacionamiento de vehículos en San Isidro - Porras Ramirez, Diego Jose (2020)
During the last decade the demand for parking services in Lima has increased, especially in the San Isidro district, despite the scarcity of parking spaces and the lack of parking facilities. The parking service chain "Los Portales" has invested in this business more than a million dollars on average in the Lima market, in the same way, there are other companies that provide this service and remain operational due to having an influx of public that has been maintained over time. Taking into account that there is no satisfaction on the part of the clients in the provision of this service and knowing the requirements of the infrastructure and equipment that are needed for its implementation, the decision was made to develop this project with the objective of evaluating financial and economically the business idea based on the characteristics presented in the content throughout this study. The parking service is aimed at adults of any socioeconomic level that goes to the district of San Isidro, providing the services of parking and monitoring their vehicles, focusing on providing quality customer service, also, meeting the proposed objectives and creating a whole comforting experience from the first point of contact. The location of the service premises is very important for the develop of the parking since the influx of customers will rely on it. For the determination of the same, micro and macro localization factors will be applied, calculation of unsatisfied demand together with a field analysis. Once the location is defined, the target audience will be measure. For this, data from secondary sources of the Peruvian Association of Market Research Companies (APEIM), The Citizen Observatory Lima, and the Tax Administration Service (SAT) are used, using the linear projection method to determine the Target market for the next four years. The size of this study will provide elementary information about the amount of demand to be expected, how much requirement we can satisfy with a limiting installed capacity and a monthly break-even point to overcome. On the other hand, in this study we will detail the equipment to be used, the extension of the plant and the elaboration of the general plan will be specified. The company will be headed by a manager, who will be the sole shareholder of the business. A legal entity will be initiated to start this entrepreneurship and the earnings tax regime will be the general one. The economic NPV and IRR, NPV and financial IRR, recovery period and cost / benefit ratio will be analyzed. Through the sensitivity analysis, three events will be compared: low risk, medium risk and high risk; in order to measure the sensitivity of net profits and the IRR respecting to a variation in sales profit and the Cok. As a result, it is obtained that this study is profitable, having a useful life of five years, financing 60% of the total expense, achieving a WACC of 6.16%, an Economic NPV of S/ 4 371 525, a Financial NPV of S/ 4 522 186 and a return that amounts to an Economic IRR of 36,21% and a Financial IRR of 65,03%.